Microwave heating type concrete as well as preparation method and application thereof

By using microwave heating concrete, the existing snow removal and ice removal methods are solved, and the problems of low efficiency, high cost and environmental pollution are achieved, efficient and environmentally friendly ice and snow melting effects are achieved, and the road surface strength and conductive properties are improved.

CN119683960AActive Publication Date: 2025-03-25JIAHUA SPECIAL CEMENT
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510007692.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-03-25
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The existing snow removal and ice removal methods have problems such as low efficiency, high cost, environmental pollution and road damage, especially in extreme winter conditions, which are difficult to effectively solve the road ice and snow problems.

Method used

Microwave heating concrete is used. This material combines graphene, carbon fiber, fly ash and other components through specific formulations and preparation methods to achieve high conductivity and self-heating functions, and is suitable for melting ice and snow and other scenarios that require heating.

Benefits of technology

It achieves efficient melting of ice and snow, reduces production costs and environmental pollution, improves road surface strength and conductivity, and is suitable for road construction under extreme winter conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683960A_ABST
    Figure CN119683960A_ABST
Patent Text Reader

Abstract

The invention discloses microwave heating type concrete as well as a preparation method and application thereof, and belongs to the technical field of building materials. The microwave heating type concrete is prepared from 5-20 mm tailings, coal gangue, 2-5 mm tailings, 0-2 mm tailings, fly ash, steel slag, high-iron-phase Portland cement clinker, high-belite sulfur aluminum clinker, desulfurized gypsum, caustic soda waste residues, solid waste, graphene, palmitic acid, a water reducing agent, carbon fibers and an electrolyte solvent. The 5-20 mm tailings, the 2-5 mm tailings and the 0-2 mm tailings are tailings of metal ores such as pyrite and chalcopyrite or graphite ores, and the prepared concrete is high in strength and excellent in conductivity and can be applied to pavement of a pavement needing to be heated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to microwave-heated concrete and a preparation method and application thereof. Background Art

[0002] Transportation is the foundation of the national economy. The highway transportation network can connect the production and life of the entire region and plays a vital role in the development of the national economy. Due to a series of meteorological disasters such as heavy rainfall, high temperature, snow, and ice, the normal passage of road traffic is often seriously affected.

[0003] At present, the snow and ice removal methods commonly used in countries around the world can be roughly divided into mechanical methods, chemical methods and thermal methods.

[0004] (1) Mechanical method Mechanical method is a method that uses mechanical devices to directly act on the snowy road surface to remove ice and snow. It is a more common snow removal method. Snowplows are divided into plow type, rotor type, and brush type according to their structure. These large snow removal equipment have high snow removal efficiency and high degree of mechanization, but for icy roads where the ice layer and the road surface are closely combined, snowplows cannot directly and effectively separate the ice layer from the road surface. In addition, the mechanical method has a large mechanical force, which is easy to cause physical damage to the road surface.

[0005] (2) Chemical method The chemical method is to spread snow-melting agents to lower the freezing point of the solution on the road surface, delay the formation of adhesion between the ice layer and the road surface, and achieve the purpose of snow and ice removal. Deicing salt generally contains sodium chloride (NaCl), magnesium chloride (MgCl2) and calcium chloride (CaCl2), but most snow-melting materials are generally ineffective in snow removal at low temperatures, and the salt will flow to both sides of the road with the melted snow, which can easily cause serious erosion of the concrete road surface and surrounding concrete ancillary facilities, reducing the mechanical properties of the road surface. In addition, the snow-melting materials flowing to the roadside with the melted ice water can easily cause environmental pollution and be detrimental to vegetation growth.

[0006] (3) Thermal method The thermal method is to heat the heated materials inside the road, and the road surface heats up to melt ice and snow, thereby removing ice and snow. According to different heating methods, it is divided into internal heating and external heating. Internal heating is to bury the heating body inside the road. Some scholars use steel fiber and graphite as conductive fillers for conductive concrete, pour a 9cm thick electric heating concrete layer on the top of two existing parking ramps in Harbin, and try to use low-voltage power supply for the first time to de-ice under extreme winter conditions. However, this method is costly, difficult to construct, and consumes a lot of energy. Some scholars have summarized the resistivity of conductive concrete when used for melting snow and ice. The use of silver powder, iron powder, copper powder and low-grade pyrite can reduce the resistivity of concrete and improve the conductive properties, but each has its own advantages and disadvantages. The external heating method uses infrared radiation to heat the pavement, but this method has low heating efficiency and will cause the road surface to age. In addition, most devices use liquefied gas as the heat source for infrared heating, so the vehicle-mounted performance is poor. Some people also use the airflow ejected from aircraft engines to melt ice and snow and blow dry the road to improve efficiency. However, aircraft engines are expensive and can easily burn roadside green belts, making them less practical. Summary of the invention

[0007] The purpose of the present invention is to improve the above technical problems. The present invention provides a microwave heated concrete and a preparation method thereof. The obtained microwave heated concrete has high strength and excellent electrical conductivity and can be used in paving roads that require heating.

[0008] The present invention is achieved through the following technical solutions: A microwave-heated concrete, comprising, by weight: 20-25 parts of 5-20mm tailings, 12-18 parts of coal gangue, 2-5mm tailings 4-8 parts, 0-2mm tailings 30-37 parts, Fly ash 0.9-1.5 parts, 4-8 parts of steel slag, 2-5.5 parts of high iron phase silicate cement clinker, 1-2 parts of high-belite sulphur-aluminium clinker, Desulfurized gypsum 0.8-1.6 parts, 0.2-0.7 parts of caustic soda waste residue, Solid waste 0.4-0.8 parts, Graphene 0.02-0.07 parts, Palmitic acid 0.1-0.2 parts, Water reducing agent 0.1-0.2 parts, Carbon fiber 0.01-0.05 parts, 4-9 parts of electrolyte solvent, The 5-20 mm tailings, 2-5 mm tailings and 0-2 mm tailings are all tailings of metal ores such as pyrite and chalcopyrite or graphite ores.

[0009] Furthermore, the 5-20 mm tailings, 2-5 mm tailings and 0-2 mm tailings have a compressive strength greater than 100 MPa and a water absorption rate less than 0.1%.

[0010] Furthermore, the coal gangue is solid waste discharged during coal mining or coal washing, and the porosity of the coal gangue is 15-25%, the compressive strength is greater than 80 MPa, and the particle size is 2-5 mm.

[0011] Furthermore, the fly ash is the bottom ash collected by the flue gas purification system during the waste incineration process and the bottom ash settled at the bottom of the flue and chimney. The specific surface area of ​​the fly ash is 600-1000m 2 / kg, calcium content is greater than 35%.

[0012] Furthermore, the content of tetracalcium aluminoferrate in the high-iron phase silicate cement clinker is greater than 20%, and the content of tricalcium aluminate is less than 3%; the content of dicalcium silicate in the high-belite sulphoaluminate clinker is greater than 45%, and the content of calcium sulphoaluminate is 30-50%.

[0013] Furthermore, the gypsum is desulfurized gypsum, and the content of calcium sulfate dihydrate is greater than 94%, and the content of calcium carbonate is greater than 1%.

[0014] Furthermore, the waste residue is waste residue produced during alkali production or alkali treatment, and the content of sodium hydroxide and potassium hydroxide in the waste residue is greater than 5%; the solid waste is dust collected by the dust collector during limestone crushing production, and the specific surface area of ​​the solid waste is 500-800m 2 / kg; the graphene is multilayer graphene with a layer number greater than 15, and the particle size of the graphene is 0.05-2mm.

[0015] Furthermore, the palmitic acid is industrial grade palmitic acid, with a melting point less than 63° C. and a purity greater than 98%; the water reducer is a polycarboxylate water reducer, with a water reduction rate greater than 45%.

[0016] A method for preparing microwave-heated concrete comprises the following steps: S1. Prepare the raw materials according to the above formula and set aside; S2. Take steel slag, high iron phase silicate cement clinker, high belite sulphoaluminum clinker and palmitic acid according to the mass ratio and put them into the ball mill for grinding until the specific gravity is 270-320m 2 / kg, 45μm sieve residue is greater than 15% to obtain material 1; S3, take caustic soda waste residue and graphene and mix them thoroughly, add appropriate amount of water to cover the mixed material, stir thoroughly for 8-12h, and then directly dry for standby use to obtain material 2; S4, taking coal gangue, carbon fiber, dried material 2, fly ash and solid waste and mixing them thoroughly for 5-8 hours to obtain material 3; S5. Take the remaining material, mix it thoroughly with material one and material three, and then shape it into microwave-heated concrete.

[0017] Furthermore, as mentioned above, the microwave-heated concrete is used in the paving of road surfaces that require heating. The microwave-heated concrete can achieve self-heating of the concrete, which is particularly suitable for melting ice and snow or in other scenarios that require heating.

[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. In the present invention, a large amount of solid wastes such as ore dressing tailings, coal gangue, fly ash, steel slag, caustic soda waste residue, limestone crushing dust solid waste, etc. are utilized, which greatly reduces the production cost of microwave-heated concrete and achieves energy conservation and emission reduction. In this scheme, the grinding fineness of the cementitious material is controlled, the grinding energy consumption is reduced and the later strength is guaranteed. At the same time, fly ash and limestone crushing dust are used as fillers to achieve continuous grading of cementitious materials, improve density, and reduce harmful pores. At the same time, limestone fine powder solid waste has a certain water-reducing effect. Combined with the close stacking of materials, it further reduces the water demand and the amount of water reducer, while improving the overall strength.

[0019] 2. In the present invention, the coal gangue is fully mixed with carbon fiber, graphene and fly ash. The carbon fiber and fly ash enter the internal pores of the coal gangue and the interlayers of the graphene during the mixing process. After hydration, the carbon fiber can effectively strengthen the connection between the graphene and the coal gangue and other aggregates, thereby increasing the strength of the concrete. The fly ash has a smaller particle size and is rapidly hydrated. In addition, the calcium sulfoaluminate in the high-belite sulfoaluminate clinker can also be rapidly hydrated. The gypsum in the system can also promote the hydration of calcium sulfoaluminate to form calcium aluminate. The steel slag is activated by alkali and sulfate. Under the action of ferroalumina, strength can be quickly formed. Tetracalcium aluminoferrite is also a mineral that hydrates faster. Under the joint action of these substances, the system has higher early strength, which reduces the maintenance cost of the material. At the same time, due to the presence of coal gangue and palmitic acid, the internal pores can provide space for temperature strain and prevent temperature cracks caused by excessive hydration. The dicalcium silicate in high-belite sulphoaluminum and the dicalcium silicate and tricalcium silicate in high-iron phase ordinary Portland cement clinker can effectively supplement the later strength, so that the whole system has high early strength, development in the medium term, and guarantee in the later period.

[0020] 3. In the present invention, graphene is intercalated with caustic soda waste slag, so that sodium hydroxide, sodium carbonate, sodium chloride and oxides such as iron and aluminum in the caustic soda waste slag enter the graphene interlayer. The rapid hydration of fly ash can also assist in solidifying the solute. The treated graphene has ionic polarity. In addition, fly ash, high-iron phase ordinary silicate cement clinker, high-belite sulphoaluminate cement clinker, steel slag, desulfurized gypsum, caustic soda waste slag and electrolyte solvents are all polar materials, which can be used to achieve self-heating of concrete, melt ice and snow, or be applied in other scenarios requiring heating through microwaves.

[0021] 4. In the present invention, graphene itself can achieve good electrical conductivity through electronic conduction, and after combined with oxidation intercalation treatment, it has ionic conductivity. Carbon fiber and fly ash enter the graphene interlayer and the internal pores of coal gangue to improve the stability of conductivity. Other substances such as steel slag, fly ash and tailings also have certain electrical conductivity. The prepared cementitious material has good electrical conductivity, and electric heating can be used as compensation to ensure the heating performance of the material together with microwave heating.

[0022] 5. In the present invention, the energy consumption of grinding is further reduced by adding palmitic acid to assist grinding during the grinding process. During the grinding process, as the temperature rises, the palmitic acid phase changes and absorbs heat, which reduces the material temperature, ensures the grinding efficiency, and reduces safety hazards. Palmitic acid can also help concrete corrosion resistance and improve the sealing performance, and strengthen the comprehensive performance of concrete. In addition, during the heating process, the palmitic acid phase change function can also reduce energy consumption and ensure the long-term stability of concrete. Palmitic acid is heated during the off-peak period to melt the palmitic acid, absorb a large amount of heat for storage, and can be solidified and released by the palmitic acid during the peak period of electricity consumption, reducing the working time during the peak period of electricity consumption. At the same time, when the temperature is high, the palmitic acid melts, which reserves space for the deformation caused by the heating of the concrete, and can prevent the concrete from cracking.

[0023] 6. In the present invention, the prepared concrete can also be cured by microwave or conductive heating under low temperature conditions to improve early strength, realize construction in winter, and shorten the construction period. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the microscopic morphology of the concrete prepared in Group 1 of Example 1. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0026] In the present invention, a microwave-heated concrete comprises, by weight: 20-25 parts of 5-20mm tailings, 12-18 parts of coal gangue, 2-5mm tailings 4-8 parts, 0-2mm tailings 30-37 parts, Fly ash 0.9-1.5 parts, 4-8 parts of steel slag, 2-5.5 parts of high iron phase silicate cement clinker, 1-2 parts of high-belite sulphur-aluminium clinker, Desulfurized gypsum 0.8-1.6 parts, 0.2-0.7 parts of caustic soda waste residue, Solid waste 0.4-0.8 parts, Graphene 0.02-0.07 parts, Palmitic acid 0.1-0.2 parts, Water reducing agent 0.1-0.2 parts, Carbon fiber 0.01-0.05 parts, 4-9 parts of electrolyte solvent; In the present invention, the 5-20mm tailings, 2-5mm tailings and 0-2mm tailings are all tailings of one or more metal ore in pyrite and chalcopyrite, or tailings of graphite ore. In the following embodiments, the 5-20mm tailings, 2-5mm tailings and 0-2mm tailings are all tailings including pyrite and chalcopyrite for experiment. And the 5-20mm tailings, 2-5mm tailings and 0-2mm tailings are tailings with a compressive strength greater than 100MPa and a water absorption rate less than 0.1%.

[0027] In the present invention, the coal gangue is solid waste discharged during coal mining or coal washing, and the porosity of the coal gangue is 15-25%, the compressive strength is greater than 80 MPa, and the particle size is 2-5 mm. In the following embodiments, the coal gangue used has a porosity of about 18%, a compressive strength of about 80 MPa, and a particle size of 2-5 mm.

[0028] In the present invention, the fly ash is the bottom ash collected by the flue gas purification system during the waste incineration process and the bottom ash settled at the bottom of the flue and chimney. The specific surface area of ​​the fly ash is 600-1000m 2 / kg, the calcium content is greater than 35%. In the following examples, the specific surface area of ​​the fly ash used is about 850m 2 / kg, the calcium content is about 40%.

[0029] In the present invention, the content of tetracalcium aluminoferrate in the high-iron phase silicate cement clinker is greater than 20%, and the content of tricalcium aluminate is less than 3%; the content of dicalcium silicate in the high-belite sulfate cement clinker is greater than 45%, and the content of calcium sulfoaluminate is 30-50%. In the following embodiments, the high-iron phase silicate cement clinker used is a cement clinker with a tetracalcium aluminoferrate content of about 22%, a tricalcium aluminate content of about 2.8% and conforming to GB / T21372-2024 "Silicate Cement Clinker"; the high-belite sulfate cement clinker is a cement clinker with a dicalcium silicate content of about 48%, a calcium sulfoaluminate content of about 35% and conforming to GB / T 37125-2018 "Sulphoaluminate Cement Clinker".

[0030] In the present invention, the gypsum is desulfurized gypsum, and the content of calcium sulfate dihydrate is greater than 94%, and the content of calcium carbonate is greater than 1%. In the following embodiments, desulfurized gypsum with a content of calcium sulfate dihydrate greater than 94% and a content of calcium carbonate greater than 1% is used for specific experiments.

[0031] In the present invention, the waste residue is the waste residue produced in the process of alkali production or alkali treatment, and the content of sodium hydroxide and potassium hydroxide in the waste residue is greater than 5%. In the following embodiments, the content of sodium hydroxide and potassium hydroxide in the waste residue used is about 7%. The solid waste is the dust collected by the dust collector in the limestone crushing production process, and the specific surface area of ​​the solid waste is 500-800m 2 / kg.

[0032] In the present invention, the graphene is a multilayer graphene with a number of layers greater than 15, and the particle size of the graphene is 0.05-2 mm. In the following embodiments, the particle size of the graphene used is about 1 mm.

[0033] In the present invention, the palmitic acid is industrial grade palmitic acid, with a melting point of less than 63°C and a purity of more than 98%. In the following examples, the palmitic acid is industrial grade premium palmitic acid produced by Wuhan Jiyesheng Chemical Co., Ltd.; the water reducer is a polycarboxylate water reducer, with a water reduction rate of more than 45%. In the following examples, the polycarboxylate water reducer used is Sika 556p.

[0034] In the following embodiments, the electrolyte solvent is one or more of ferric sulfate, sodium sulfate, sodium hydroxide, and potassium hydroxide as solutes, tap water is used as solvent, and the mass fraction of the weak electrolyte solvent is 2-5wt%. In the following embodiments, the electrolyte solvent is ferric sulfate with a mass fraction of 5wt% for experiment.

[0035] Example 1 A microwave-heated concrete is prepared by taking raw materials according to the raw material proportions in each group in Table 1 below, and using the following preparation method to obtain the microwave-heated concrete.

[0036] A method for preparing microwave-heated concrete comprises the following steps: S1. Prepare the raw materials according to the various recipes in Table 1 and set aside; S2. Put steel slag, high iron phase silicate cement clinker, high belite sulphoaluminum clinker and palmitic acid into a ball mill according to the mass ratio for grinding until the specific surface area and 45 μm sieve residue are shown in Table 2, thereby obtaining material 1; S3, take caustic soda waste residue and graphene and mix them thoroughly, add appropriate amount of water to cover the mixed material, stir thoroughly for 8-12h, and then directly dry for standby use to obtain material 2; S4, taking coal gangue, carbon fiber, dried material 2, fly ash and solid waste and mixing them thoroughly for 5-8 hours to obtain material 3; S5. Take the remaining material, mix it thoroughly with material one and material three, and then shape it into microwave-heated concrete.

[0037] Table 1 Table 2 Comparative Example 1 The only difference between this comparative example and Group 1 in Example 1 is that all tailings are 5-20 mm tailings, and the other formulas and preparation methods are the same.

[0038] Comparative Example 2 The only difference between this comparative example and Group 1 in Example 1 is that the fly ash and limestone crushing dust collection are replaced by 0-2 mm tailings materials of equal mass, and the other formulas and preparation methods are the same.

[0039] Comparative Example 3 The only difference between this comparative example and Group 1 in Example 1 is that the carbon fiber is replaced with graphene of equal mass, and the other formulas and preparation methods are the same.

[0040] Comparative Example 4 The only difference between this comparative example and Group 2 in Example 1 is that the caustic soda waste residue is replaced with 0-2 mm tailings of equal mass, and the other formulas and preparation methods are the same.

[0041] Comparative Example 5 The only difference between this comparative example and the second group in Example 1 is that the steel slag and fly ash are replaced with 0-2 mm tailings of equal mass, and the other formulas and preparation methods are the same.

[0042] Comparative Example 6 The only difference between this comparative example and Group 3 in Example 1 is that the high-iron phase silicate cement clinker is replaced with ordinary silicate cement clinker of equal mass, and the other formulas and preparation methods are the same.

[0043] The compressive strength of concrete after standard curing of 3d, 28d and 56d was tested with reference to GB / T 50107-2010 "Standard for Inspection and Evaluation of Concrete Strength". The 3d compressive strength of concrete was tested by curing in a KQ6000 adjustable industrial box-type microwave heating device at low temperature (5℃) with the power set to 20kW and the frequency set to 2.45GHz. The air content and slump of concrete were tested with reference to GB 50204-2015 "Code for Acceptance of Construction Quality of Concrete Structure Engineering". The resistivity of concrete was tested with reference to ASTM C177-18. The microwave heating performance was tested by placing a standard test block after standard curing of 28d in a KQ6000 adjustable industrial box-type microwave heating device with the power set to 20kW and the frequency set to 2.45GHz, and recording the temperature after heating for ten minutes.

[0044] The test results refer to Table 3, and the microscopic morphology of the concrete prepared in Group 1 of Example 1 refers to Figure 1 .

[0045] Table 3 It can be seen from Table 3 that by adopting the formula of this scheme, microwave-heated concrete with high strength (compressive strength > 65 MPa after 56 days of curing) can be obtained, and both have high early strength and excellent electrical conductivity (resistivity less than 100 Ω·m).

[0046] It can be seen from Example 1 and Comparative Example 1 that the use of a multi-graded tailings combination can effectively reduce the voids inside the concrete, enhance the continuity of the internal material, increase the early and late strength, and reduce the resistivity. Such a multi-grade tailings combination also increases the proportion of tailings as much as possible.

[0047] It can be seen from Example 1 and Comparative Example 2 that the use of fly ash and limestone crushed dust collection powder is beneficial to increasing early and late strength and reducing resistivity. Further research found that fly ash and limestone crushed dust collection powder can effectively fill the micropores of concrete, reduce the air content, and is beneficial to increasing early and late strength and reducing resistivity.

[0048] It can be seen from Example 1 and Comparative Example 3 that the use of carbon fiber increases the strength of concrete and reduces resistivity. Further research found that carbon fiber can increase the connection between materials, increase the strength of concrete, and carbon fiber has good conductivity and reduces resistivity.

[0049] It can be seen from Example 2 and Comparative Example 4 that the use of caustic soda waste residue can significantly increase the conductivity. Further research has found that caustic soda waste residue can stimulate the activity of steel slag, fly ash, etc. to improve strength. At the same time, caustic soda waste residue can intercalate graphene to increase conductivity. Caustic soda waste residue itself contains a large amount of electrolyte, which can also help improve conductivity.

[0050] It can be seen from Example 2 and Comparative Example 5 that fly ash and steel slag can be used as cementitious materials to improve strength after being excited. At the same time, fly ash can reduce the micropore size and further supplement the strength. In addition, steel slag and fly ash are also conductive and can increase the conductive performance.

[0051] It can be seen from Example 3 and Comparative Example 6 that the use of high-iron phase silicate cement clinker can increase the early strength, while the higher iron content can increase the electrical conductivity and microwave heating performance.

[0052] From the above, it can be seen that the microwave heated concrete formula of the present invention, combined with the microwave heated concrete obtained by the preparation method thereof, has high early strength and excellent electrical conductivity, and can be used in the paving of pavements requiring heating. At the same time, a large amount of solid waste such as ore dressing tailings, coal gangue, fly ash, steel slag, caustic soda waste residue, limestone crushing dust collection solid waste, etc. is utilized, which significantly reduces the cost and has strong practicality.

[0053] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.

Claims

1. A microwave-heated concrete, characterized in that: By mass, including 20-25 parts of 5-20mm tailings, 12-18 parts of coal gangue, 2-5mm tailings 4-8 parts, 0-2mm tailings 30-37 parts, Fly ash 0.9-1.5 parts, 4-8 parts of steel slag, 2-5.5 parts of high iron phase silicate cement clinker, 1-2 parts of high-belite sulphur-aluminium clinker, Desulfurized gypsum 0.8-1.6 parts, 0.2-0.7 parts of caustic soda waste residue, Solid waste 0.4-0.8 parts, Graphene 0.02-0.07 parts, Palmitic acid 0.1-0.2 parts, Water reducing agent 0.1-0.2 parts, Carbon fiber 0.01-0.05 parts, 4-9 parts of electrolyte solvent, The 5-20 mm tailings, 2-5 mm tailings and 0-2 mm tailings are all tailings of metal ores such as pyrite and chalcopyrite or graphite ores.

2. The microwave-heated concrete according to claim 1, characterized in that: The 5-20 mm tailings, 2-5 mm tailings and 0-2 mm tailings have a compressive strength greater than 100 MPa and a water absorption rate less than 0.1%.

3. The microwave-heated concrete according to claim 1, characterized in that: The coal gangue is solid waste discharged during coal mining or coal washing. The porosity of the coal gangue is 15-25%, the compressive strength is greater than 80MPa, and the particle size is 2-5mm.

4. The microwave-heated concrete according to claim 1, characterized in that: The fly ash is the bottom ash collected by the flue gas purification system during the waste incineration process and settled at the bottom of the flue and chimney. The specific surface area of ​​the fly ash is 600-1000m 2 / kg, calcium content is greater than 35%.

5. The microwave-heated concrete according to claim 1, characterized in that: The content of tetracalcium aluminoferrate in the high-iron phase silicate cement clinker is greater than 20%, and the content of tricalcium aluminate is less than 3%; the content of dicalcium silicate in the high-belite sulphoaluminate clinker is greater than 45%, and the content of calcium sulphoaluminate is 30-50%.

6. The microwave-heated concrete according to claim 1, characterized in that: The gypsum is desulfurized gypsum, wherein the content of calcium sulfate dihydrate is greater than 94% and the content of calcium carbonate is greater than 1%.

7. The microwave-heated concrete according to claim 1, characterized in that: The waste residue is the waste residue produced in the process of alkali production or alkali treatment, and the content of sodium hydroxide and potassium hydroxide in the waste residue is greater than 5%; the solid waste is the dust collected by the dust collector in the limestone crushing production process, and the specific surface area of ​​the solid waste is 500-800m 2 / kg; the graphene is multilayer graphene with a layer number greater than 15, and the particle size of the graphene is 0.05-2mm.

8. The microwave-heated concrete according to claim 1, characterized in that: The palmitic acid is industrial grade palmitic acid, with a melting point of less than 63° C. and a purity of more than 98%; the water reducer is a polycarboxylate water reducer, with a water reduction rate of more than 45%.

9. A method for preparing microwave-heated concrete, characterized in that: The steps include: S1. Prepare the raw materials according to the formula of claim 1 and set aside; S2. Take steel slag, high iron phase silicate cement clinker, high belite sulphoaluminum clinker and palmitic acid according to the mass ratio and put them into the ball mill for grinding until the specific gravity is 270-320m 2 / kg, 45μm sieve residue is greater than 15% to obtain material 1; S3, take caustic soda waste residue and graphene and mix them thoroughly, add appropriate amount of water to cover the mixed material, stir thoroughly for 8-12h, and then directly dry for standby use to obtain material 2; S4, taking coal gangue, carbon fiber, dried material 2, fly ash and solid waste and mixing them thoroughly for 5-8 hours to obtain material 3; S5. Take the remaining material, mix it thoroughly with material one and material three, and then shape it into microwave-heated concrete.

10. Use of the microwave-heated concrete according to any one of claims 1 to 9 in paving a road surface that requires heating.

Citation Information

Patent Citations

  • Full-steel slag electrically-conductive concrete

    CN102503327A

  • Electroconductive concrete

    CN106866082A

  • All-solid-waste clinker-free cementing material, conductive mortar and preparation method of all-solid-waste clinker-free cementing material

    CN114671633A

  • Conductive concrete based on solid waste conductive phase and preparation method thereof

    CN117776634A